CFD optimization of horizontal continuous stirred-tank (HCSTR) reactor for bio-hydrogen production. (13th April 2017) - Ri, Pong-Chol; Ren, Nan-Qi; Ding, Jie; Kim, Jong-Su; Guo, Wan-Qian
Abstract: This paper described the design on the lab-scale horizontal continuous stirred-tank reactor (HCSTR) that the effective working volume is relatively large and the performance is stable at lower agitating speed. Using the Computational Fluid Dynamics (CFD) simulation with an ethanol-type fermentation process experiment we determined the optimal agitating speed range for the bio-hydrogen production from analysis on the flow pattern generated at the various agitating speed conditions and select and the suitable three phase separator design has been constructed for gas–liquid–solid three phase separations. The experimental results in the designed bioreactor show that the agitating speeds of 50 rpm is most suited for economical bio-hydrogen production and three phase separation. It was consistent with the prediction from CFD simulation. The information obtained from this study is expected to provide basic knowledge on the optimal design of bioreactor and three phase separator aimed for scale up of the continuous stirred-tank reactor for bio-hydrogen production. Highlights: The horizontal CSTR is designed. The optimal agitating speed is determined by CFD simulations. The suitable three phase separator is selected by CFD simulations. The rationality of the reactor was validated through experiments.